Um estudo em Ierecê Barbosa: as contribuições pedagógicas em “O Leilão” - Gonçalves, Carmen Érica Lima de Campos (2020)
This work starts from the perspective of considering alternatives in research-training for which it brings elements of analytical psychology as an epistemology to explore the (self) formation of teachers considering a literary novel whose authorship is from an Amazonian research teacher, focusing on to situate a reality close to the public to whom it is addressed, in addition to involving aspects of self-knowledge and life history that emerge in authoring processes and contribute to initial and continuing teacher training. In this way, the research was developed from the purposes: a) To Storytell the researcher teacher Ierecê Barbosa, considering both aspects of her personal and professional life; b) To Present the results of the analytical study done in the investigated literary work and c) To Talk about the socialization of the results in the analytical study done, taking as a guiding reference a Colloquium as a professional training strategy for teachers; in order to master goal of Analyzing the Pedagogical in “O Leilão” - a literary work by a researcher teacher - using the respective knowledge analyzed in a Colloquium, as a professional training strategy for teachers, conduced to answer the initial problem of How the Pedagogical is perceived in “O Leilão”, a literary work by a researcher teacher and how can this analyzed knowledge could be used in a Colloquium as a professional training strategy for teachers? On this procedure, Structural (or Objective) Hermeneutic Analysis was used on the generation of significant units by sub-phenomena (Archetypes, Transcendent Function) that revealed the key phenomenon (Individuation Process) and for this way established convergent conceptual relationships for the continued (self)training education involved to the individual ontology and its implication for the collective through Education by Example. The content was applied in two academic events aimed at teachers in training, as an academic education gadget, using the Colloquium structure, which analysis was conducted by the same way of the novel analysis by the participants written records, triangulated by the ethological study (no verbal language and behavior) of the participants, in order to check the content emerged through it and the receptivity on the theme by them; whose potential allowed the Educational Product arising from this research to be constituted, as it indicated the intended formative effectiveness and; was materialized in a planner scheduler/a guiding planner book called “Colloquium as a Training Strategy” which function is supporting others instructors who intend to invest on the same training strategy. The process revealed consistency for teacher training processes due to the approach with the storytelling and the psychobiography, as well as potentials of ethological study for conducting activities with students, both aiming at Jungian Education by Example; in which the literary work used as an excuse for this research served satisfactorily for this work and for the public that participated, indicating potential in the paradidactic use in the High Education, Lato and Stricto Sensu graduate, within an epistemic-methodological structure in line with the intended intention.